PENGARUH KUALITAS PRODUK DAN PROMOSI PENJUALAN TERHADAP MINAT BELI ULANG DI KEDAI FOOD SPICY CHILI KOTA PASURUAN - Siska, Juliana; Pudyaningsih, A. Ratna; Erwantiningsih , Eni (Jurnal Pijar, 2024)
Data from the Ministry of Cooperatives and SMEs for 2023 states that Indonesia has 65.5 million MSMEs, therefore business actors must be able to retain their consumers so they do not switch to other products. One way is to stimulate consumers to have an interest in repurchasing their products. Food Spicy Chili is a food shop that focuses on selling spicy food where spicy food is very popular with the public. The aim of this research is to determine the effect of product quality and sales promotions on repurchase interest at the Kedai Food Spicy Chili. The results of this research show that product quality and sales promotion simultaneously have a positive influence on repurchase interest with a significance value of 0.000 and a coefficient of determination (R2) of 70.5%. Product quality has a positive effect on repurchase interest with a significance value of 0.000, and sales promotions have a positive effect on repurchase interest with a significance value of 0.033.